2013
DOI: 10.1111/imj.12104
|View full text |Cite
|
Sign up to set email alerts
|

When do we transfuse cryoprecipitate?

Abstract: Background The 2001 National Health and Medical Research Council/Australasian Society of Blood Transfusion Clinical Practice Guidelines for cryoprecipitate are being updated, and cryoprecipitate has been incorporated into new Patient Blood Management modules. Aims This clinical audit sought to clarify current cryoprecipitate use in Victoria, Tasmania and the Australian Capital Territory; assess adherence to guidelines; and gain insights into deviations from recommended practice. This information can be utilise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Cryoprecipitate has a long history of use in many countries, including the United Kingdom, the United States, and Republic of Korea. In Australia, it has been reported that 22% of cryoprecipitate consumption is in the setting of cardiac surgery . However, there is little robust evidence of the efficacy of cryoprecipitate in increasing fibrinogen levels and few recommendations on appropriate transfusion amounts 6‐8.…”
mentioning
confidence: 99%
“…Cryoprecipitate has a long history of use in many countries, including the United Kingdom, the United States, and Republic of Korea. In Australia, it has been reported that 22% of cryoprecipitate consumption is in the setting of cardiac surgery . However, there is little robust evidence of the efficacy of cryoprecipitate in increasing fibrinogen levels and few recommendations on appropriate transfusion amounts 6‐8.…”
mentioning
confidence: 99%
“…[14] Similar transfusion audits conducted in other countries also suggested that cryoprecipitate is often found not aligned to published guideline. [6151617] Nonetheless, this study outlined the main contributor for the practice inappropriateness is the absence of pretransfusion fibrinogen level estimation.…”
Section: Discussionmentioning
confidence: 90%
“…When the fibrinogen-based transfusion trigger was increased to 1.5 g/L, the rate of appropriateness improved to 61%. [17] In postpartum bleeding cases, studies showed that fibrinogen level <2 g/L were strongly associated with high risk of severe bleeding, with a predictive value of 100%. [25]…”
Section: Discussionmentioning
confidence: 99%
“…For studies of management strategies (Table ), corresponding rates of overuse comprised: 14–74% of blood product infusions among patients with various conditions ( n = 3) 15–55% of older patients receiving at least one inappropriate medication ( n = 7) 34% of chronically prescribed medications of various classes among older patients ( n = 1) 99% of ondansetron prescriptions in patients with severe emesis ( n = 1) 63–90% of regular prescriptions for gastric acid suppressants in patients admitted to intensive care units ( n = 2) 34% of regular prescriptions of direct oral anticoagulants in patients with various conditions ( n = 1) 21% of antimicrobial prescriptions for patients with acute infections ( n = 1) 52% of prescriptions for inhaled corticosteroids in patients with mild chronic obstructive pulmonary disease ( n = 1) 55% of instances of high flow oxygen therapy administered to patients with chronic obstructive pulmonary disease ( n = 1) 33% of overnight admissions to medical assessment and planning unit for monitoring and evaluation relating to patients presenting to emergency department with undifferentiated chest pain and low coronary risk ( n = 1) 10–64% of end‐of‐life care admissions featuring the administration of futile interventions ( n = 3) …”
Section: Studies Of Inappropriate Use Of Investigationsmentioning
confidence: 99%